Different body mass indexes and their relation to prognosis of early-stage breast cancer in postmenopausal Mexican-Mestizo women. Issue 2 (7th February 2021) - Cárdenas-Cárdenas, Eduardo; Tenorio-Torres, Alberto; Méndez, Juan Pablo; Orozco-Arguelles, Leticia; Leal-García, Marcela; Tejeda, María Elena; Morales, Angélica; Canto, Patricia
ABSTRACT: It has been suggested that obesity increases the incidence of metastatic breast tumors, resulting in higher rates of recurrence, and increased mortality; for that reason, the aim of this study was to investigate if different body mass indexes modified the clinicopathologic characteristics of breast cancer; as well as, the recurrence-free survival in postmenopausal Mexican-Mestizo women. Two hundred twenty postmenopausal women with operable breast cancer were included. A structured questionnaire was applied to explore the existence of potential risk factors. Body mass index (BMI) was determined in each case and patients were grouped in accordance to their BMI in: normal weight, overweight, or obesity. Kaplan–Meier survival analysis and log-rank statistic were used to estimate recurrence-free-survival differences. Hormonal receptor(+)/HER2(-) was the most frequent breast cancer in all groups. Overweight women presented a statistically significant increased risk of this molecular subtype, with an odds ratio (OR) = 5.57; 95% confidence interval (CI) = 1.54–24.86; P = .004)). In addition, the triple-negative subtype was more frequent in women with a normal BMI in comparison to women with overweight ( P = .016) or women with obesity. The heterogeneity in cancer subtypes regarding BMI was observed.